Energy efficiency and carbon footprints of rice-wheat system under long-term tillage and residue management practices in western Indo-Gangetic Plains in India. (1st April 2022) - Singh, Ranbir; Singh, Ajay; Sheoran, Parvender; Fagodiya, R.K.; Rai, Arvind Kumar; Chandra, Priyanka; Rani, Sonia; Yadav, Rajender Kumar; Sharma, P.C.
Abstract: Conventional rice-wheat cropping system (RWCS) in western Indo-Gangetic Plains (IGP) is carbon and energy intensive. A field experiment was conducted to evaluate energy budgeting, carbon footprints (CF) and greenhouse gas (GHG) emissions from RWCS under long-term tillage and residue management practices. Experiment consisted six treatment combination of tillage [conventional tillage (CT), reduced tillage (RT) and zero tillage (ZT)] and residue [with residue (+R) and without residue (–R)] namely (i) CT-R (conventional farmers' practice), (ii) CT + R, (iii) RT-R, (iv) RT + R, (v) ZT-R and (vi) ZT + R. Energy consumption ranged from 51.87 GJ ha −1 (ZT-R) to 64.91 GJ ha −1  (CT + R) and irrigation water was major energy intensive input (41–44%) followed by chemical fertilizer (32–40%). Compared to CT-R, energy use efficiency (EUE) increased by 8.7–22.4%, CF lowered by 77.9–34.3%, and GHG emission lowered by 12.8–16.3% in different treatments. Residue addition enhanced the soil carbon accumulation in ZT + R (1213 kg C ha −1 yr −1 ) and RT + R (987 kg C ha −1 yr −1 ). Overall, switching from CT–R to ZT + R lowered energy consumption (19%), GHG emission (16%) and CF (78%), making it best-bet option for climate change mitigation and global warming related environmental protection in western IGP and similar agro–ecologies. Graphical abstract: Image 1 Highlights: Energy use efficiency (EUE), Greenhouse gases (GHGs) emission and carbon footprints (CF) were analysed. Irrigation water contribute maximum (41–44%) share of input energy followed chemical fertilizers (32–40%). Conservation tillage and residue management enhanced energy productivity (15.8–21.0%) and EUE (17.1–22.4%). The CF lowered by 77.9% in zero tillage with residue to 45.2% in reduced tillage without residue. Zero tillage with residue addition is most energy efficient system with lower GHG emission and carbon footprint.